Cardiovascular risk factors among industrial workers: a cross–sectional study from eastern Nepal. Issue 1 (December 2016) - Pyakurel, Prajjwal; Karki, Prahlad; Lamsal, Madhab; Ghimire, Anup; Pokharel, Paras
Abstract Background Cardiovascular diseases (CVD) are the number one cause of death globally, more people die annually from CVDs than from any other cause. An estimated 17.5 million people died from CVD in 2012, representing 46.2 % of all NCD death globally. An accurate characteristic of the cardiovascular risk factors in a specified population group is essential for the implementation of educational campaign. However, there are no reliable CVD risk factors burden, nor of its awareness and treatment status in Nepal industrial settings. We aimed to assess cardiovascular risk factors among men age 20-59 years in one of the largest industrial corridor of Eastern Nepal. Methods A total of 494 industrial workers between ages of 20–59 years, from two industries participated in the study. Pretested semi-structured questionnaire was used to collect the information. Primary outcome was cardiovascular risk factors based on STEPS survey and study on non-communicable disease in Nepal. A semi-structured questionnaire was used to interview 494 industrial workers. Lipid profile and serum blood glucose of 406 workers and electrocardiogram of 400 workers was done. Results The prevalence of cardiovascular disease (CVD) was 13.8 %. Those who were >45 years were 2.72 times more likely to develop CVD. Those who smoked more pack year, had family history of hypertension (HTN) and consumed no fruits were 4.32, 1.90.2.47 times more likely to develop CVD. Low density Lipoprotein (LDL) level <130 was found to be protective compared to LDL level above ≥ 130. On adjusted analysis those who did not consume fruits and had high LDL level were 3.32 and 3.03 more likely to develop CVD. Conclusion There is high prevalence of CVD risk factors. Although majority of them are literate there is lack of health education and awareness among young male population in an eastern Nepal industrial setting.